Meta Analysis of Human AlzGene Database: Benefits and Limitations of Using C. elegans for the Study of Alzheimer's Disease and Co-morbid Conditions - Vahdati Nia, Behrad; Kang, Christine; Tran, Michelle G.; Lee, Deborah; Murakami, Shin (Frontiers in Genetics, 2017)
Human genome-wide association studies (GWAS) and linkage studies have identified 695 genes associated with Alzheimer’s disease (AD), the vast majority of which are associated with late-onset AD. Although orthologs of these AD genes have been studied in several model species, orthologs in the nematode, Caenorhabditis elegans, remain incompletely identified, with orthologs to only 17 AD-related genes identified in the C. elegans database, WormBase. Therefore, we performed a comprehensive search for additional C. elegans orthologs of AD genes using well-established programs, including OrthoList, which utilizes four ontology prediction programs. We also validated 680 of the AD genes as a unique gene from the AlzGene database, including 431 genes (63%) that are predicted to have orthologs in C. elegans. Another 178 human AD genes (26%) were associated with one or more other neurological diseases, including amyotrophic lateral sclerosis, multiple sclerosis, Parkinson’s disease, and schizophrenia. Of these, there were 105 genes (59%) with orthologs in C. elegans. Interestingly, three AD genes (ACE, TNF, and MTHFR) were associated with all four of the other neurological diseases. The human AD genes were enriched in three major ontology pathway groups, including lipoprotein metabolism, hemostasis, and extracellular matrix organizations, as well as in pathways that are amyloid related (NOTCH signaling) and associated with neural (neurotransmitter clearance) and immune (advanced glycation end-product receptor signaling and TRAF6-NF-kappaB) systems. Thus, the results from this study provide a potentially useful system for assessing comorbidities that may be associated with late-onset AD and other neurological conditions. The technical advantages and limitations of the ortholog searches are further discussed.